Development of UV SPectrophotometry and RP HPLC Method and Its Validation for Simultaneous Estimation of Sitagliptin Phosphate and Simvastatin in Marketed Formulation - Sharma, Sheetal (International Journal of Pharmaceutical & Biological Archive, 2012)
Development of UV-SPectrophotometry and RP HPLC Method and Its Validation for Simultaneous Estimation of Sitagliptin Phosphate and Simvastatin in Marketed Formulation